Political change in Southeast Asia : - Vatikiotis, Michael R. J. (Routledge, 1996)
Southeast Asia is a vast and complex region, comprising countries with remarkably diverse histories and cultures. Jacques Bertrand provides a fresh and highly original survey of politics and political change in this area of the world. Against the backdrop of rapid economic development and social transformation in several countries, he explores why some countries have adopted democratic institutions, while others have maintained stable authoritarian systems or accepted communist regimes. Bertrand presents a historically grounded account of capitalist countries and state-socialist countries, delving into the historical experience of individual countries, whilst simultaneously providing a comparative framework with which to draw parallels and foster a better understanding of the political and economic dynamics both within and between the countries. With powerful yet accessible analysis and detailed coverage, this book offers students and scholars a thorough and thought-provoking introduction to the political landscape of Southeast Asia.